СТРУКТУРНЫЕ ТИПЫ АНГЛИЙСКИХ ТЕРМИНОЛОГИЧЕСКИХ ЕДИНИЦ - Авезимбетова, А. (SCIENCE and SOCIETY, 2016)
The article deals with the structural peculiarities of English terminological units. The object of the investigation is the structural types of scientific-technical terms. In the result of the morphological analysis there were defined the following ways of formation of the terms: lexico-semantic, morphological, word composition and shorteming (abbreviations and acronyms)